2021
DOI: 10.1039/d1cp03349b
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism behind the stabilization of insulin by choline and geranate (CAGE) ionic liquids – computational insights into oral insulin drug formulation

Abstract: Insulin is a principle hormone that is involved in the regulation of glucose levels in the blood. Oral insulin formulation is a recent development in drug delivery systems. Biocompatible choline-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[131,141] Fortunately, choline and geranate (CAGE)-based IL formulations offer a new strategy. [55,[142][143][144] CAGE enables high-efficiency oral delivery of insulin by preventing its degradation by gastric acid and digestive enzymes, promoting paracellular transport, and increasing insulin absorption. Buccal administration of insulin-CAGE is another promising route of administration.…”
Section: Ionic Liquid-peptides and Ionic Liquid-proteinsmentioning
confidence: 99%
“…[131,141] Fortunately, choline and geranate (CAGE)-based IL formulations offer a new strategy. [55,[142][143][144] CAGE enables high-efficiency oral delivery of insulin by preventing its degradation by gastric acid and digestive enzymes, promoting paracellular transport, and increasing insulin absorption. Buccal administration of insulin-CAGE is another promising route of administration.…”
Section: Ionic Liquid-peptides and Ionic Liquid-proteinsmentioning
confidence: 99%
“…For example, the addition of a buffered choline–dihydrogen phosphate IL could substantially prolong the shelf-life of siRNA up to three months [ 73 ]. As another example, molecular simulation results indicated that CAGE could stabilize insulin by occupying the solvation shell of insulin, concomitantly exiling water molecules from the insulin surface [ 74 ]. Furthermore, an IL mixture of CAGE and choline–phenylpropanoic acid (CAPA) was designed to topically deliver siRNA for psoriasis treatment [ 10 ].…”
Section: Novel Pharmaceutical Strategies For Skin Penetrationmentioning
confidence: 99%
“…47 Using an insulin dimer, Prakash and co-workers investigated a range of CAGE IL concentrations (0.05-1.00 mole fractions). 48 Their calculations reveal that, in the presence of water, choline and geranate ions easily occupy the first solvation shell of insulin. Moreover, for the 0.30-0.50 mole fraction of CAGE IL, intermolecular hydrogen bonding (H-bonding) interactions with insulin were eliminated due to the strong interactions between the geranate ions and water molecules.…”
Section: Introductionmentioning
confidence: 99%